Distributed database systems - Chhanda Ray (New Delhi Pearson, 2012)
Distributed Database Systems discusses the recent and emerging technologies in the field of distributed database technology. The material is up-to-date, highly readable, and illustrated with numerous practical examples. The mainstream areas of distributed database technology, such as distributed database design, distributed DBMS architectures, distributed transaction management, distributed concurrency control, deadlock handling in distributed systems, distributed recovery management, distributed query processing and optimization, data security and catalogue management, have been covered in detail. The popular distributed database systems, SDD-1 and R*, have also been included.
Keywords: DBMS; Concurrency Control